2003
DOI: 10.1364/josaa.20.001841
|View full text |Cite
|
Sign up to set email alerts
|

Optical aberrations of intraocular lenses measured in vivo and in vitro

Abstract: Corneal and ocular aberrations were measured in a group of eyes before and after cataract surgery with spherical intraocular lens (IOL) implantation by use of well-tested techniques developed in our laboratory. By subtraction of corneal from total aberration maps, we also estimated the optical quality of the intraocular lens in vivo. We found that aberrations in pseudophakic eyes are not significantly different from aberrations in eyes before cataract surgery or from previously reported aberrations in healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
111
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(119 citation statements)
references
References 45 publications
(65 reference statements)
7
111
1
Order By: Relevance
“…It has been shown that ocular higher-order aberration in pseudophakic eyes is comparable with that in phakic eyes of subjects of the same age. [11][12][13] This is because standard IOLs have a positive spherical aberration, and thus add to the total ocular aberration.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that ocular higher-order aberration in pseudophakic eyes is comparable with that in phakic eyes of subjects of the same age. [11][12][13] This is because standard IOLs have a positive spherical aberration, and thus add to the total ocular aberration.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of these lenses has been reported in numerous studies performed both in vivo and in vitro showing that decentration and tilt are two frequent and important factors affecting vision to be taken into account in cataract surgery (see For example [1][2][3][4] and the references therein). To assess the optical quality of MIOLs several experimental setups were designed in which the Point Spread Function (PSF) and/or the Modulation Transfer Function (MTF), measured for the distance and the near foci, are the essential merit functions.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand the response of a MIOL to misalignments, such as tilt and decentration is a crucial issue for assessing its optical performance [6][7][8] and the tolerance to these factors is included in the battery of tests contained in the ISO 11979:2006 standard [9]. The influence of misalignments of monofocal intraocular lenses has been tested with different techniques such as using Purkinje images [10,11], Scheimpflug photography [11,12] and ray tracing [3,8,13]. However, these techniques are not easily adapted to assess the performance of decentered MIOLs.…”
Section: Introductionmentioning
confidence: 99%
“…Aberrometry has been applied recently to evaluate visual quality after cataract or refractive surgery. [8][9][10][11] Most reports related to high-order aberrations of an IOL-implanted eye measure whole-eye aberration, and yet measurements are affected by front corneal aberration, which may disrupt on-target evaluation of the IOL. We measured, compared, and evaluated whole-eye, corneal, and internal spherical aberrations of ThinOptX IOL-and Acrysof IOL-implanted eyes.…”
Section: Introductionmentioning
confidence: 99%